Analysis of Plant Seed Distribution Activities by Immigration Polytechnic Cadets in Car Free Day Activities in Tangerang - Teuku Chrismon Shavirko; Sri Kuncoro Bawono (Jurnal Abdimas Imigrasi, 2020)
The purpose of carrying out the activity of distributing plant seeds by the Immigration Polytechnic Cadets with the Class I Non TPI Tangerang Immigration Office in this car free day activity is a form of concern for the surrounding environment, especially the people of Tangerang City. The activity, which was carried out with the theme "Together to Know The Culture and Social Development of Community", was in the form of devotional work activities, distribution of plant seeds to the community, as well as the implementation of socialization related to immigration by the Class I Non TPI Tangerang Immigration Office and socialization related to Polytechnic. Immigration by Immigration Polytechnic Cadets. This activity is a form of social responsibility for the Immigration Polytechnic Cadets as new citizens of Tangerang City and their environment.